Father-Hunger: Dampak Fatherless Pada Perempuan Dewasa Awal Dalam Aspek Hubungan Romantis - Sandra Wahyudi; Siti Nurbayani; Mirna Nur Alia Abdullah (Universitas Muhammadiyah Makassar, 2024)
Individuals who are fatherless feel the loss of the important role of a father as a provider in the family, protector of the family, educator for the children, and companion to a mother. The aim of this research is to analyze the impact of the loss of the father’s role on women in their emerging adulthood in terms of romantic relationships. The research method used is qualitative with a case study research design. Data collection techniques use in-depth interviews, literature study, observation, and documentation. The data analysis carried out included the stages of data reduction, data display, and drawing conclusions. The result of this research shows that: the informants have trust issue towards men; selective in choosing partners; and are traumatized by abusive men. Apart from that, the condition of being fatherless also influences them in determining their ideal partner figure in order to fulfill the emptiness they feel due to the absence of a father figure in their life.